An early Middle Bronze Age canaanite scarab from Naḥal Aviv: the difference between Tufnell’s side types e6b and d14, and the relevance of the Heirloom paradigm for scarabs in later contexts - Brandl, Baruch (Ägypten und Levante, 2019)
The publication of a Middle Bronze Age scarab found in an Early Roman period rock-cut burial cave at Naḥal Aviv in the Upper Galilee serves as a platform for the following additional issues: The precise definition of the scarab’s side type; the possible time span of its production; the preferable chronological division for the Middle Bronze Age Canaanite scarabs; the relevance of the Heirloom Paradigm for the presence of earlier glyptic objects in later contexts.